2021
DOI: 10.19090/pp.2021.4.465-481
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Core of personality: Individual’s expression of locus of control and spirituality

Abstract: Dark personality traits are amongst the most popular research topics recently. In 2018 the Dark Core of personality was proposed as a common core to capture all aversive subclinical manifestations. In this study, we aimed at investigating how individuals with high scores on the Dark Core perceive control (i.e., internally or externally) and express their spirituality. Participants were 614 adults, mostly females (85.17%), aged from 18 to 73 years-old (M = 36.00; SD = 12.26), and identified themselves as agnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As pre-established, the three characteristics comprising the Dark Triad were related to aversive outcomes such as dysregulation strategies (i.e., aggressiveness, pessimism, and paralysis) and depressive symptomatology. Furthermore, significant correlations were found only for the external control locus, indicating that darker individuals tend to understand events as controlled by external events (Bonfá-Araujo et al, 2021a;Guo et al, 2021). Our study has two main results.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…As pre-established, the three characteristics comprising the Dark Triad were related to aversive outcomes such as dysregulation strategies (i.e., aggressiveness, pessimism, and paralysis) and depressive symptomatology. Furthermore, significant correlations were found only for the external control locus, indicating that darker individuals tend to understand events as controlled by external events (Bonfá-Araujo et al, 2021a;Guo et al, 2021). Our study has two main results.…”
Section: Discussionmentioning
confidence: 58%
“…Despite these limitations, the study showed how the dark personality could make use of dysfunctional emotion regulation strategies by behaving aggressively or ignoring problems, thus culminating in aversive consequences, and possibly blaming external circumstances. It is suggested that further studies should investigate how individuals with dark personality traits can use emotional regulation strategies to harm others, in addition to investigating the relationship between the Dark Triad and the internal locus of control, as only relationships with the external locus of control have been found (Bonfá-Araujo et al, 2021a;Rapp-Ricciardi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%